CircASPH promotes KGN cells proliferation through miR‐375/MAP2K6 axis in Polycystic Ovary Syndrome. Issue 6 (28th December 2020) - Wu, Gengxiang; Xia, Jing; Yang, Zhe; Chen, Yajie; Jiang, Wei; Yin, Tailang; Yang, Jing
Abstract: Polycystic Ovary Syndrome (PCOS) is a kind of endocrine disorder which is prevalent in adult women, so exploring more biomarkers for PCOS is imperative. Recently, circular RNA and microRNA are confirmed to be related with PCOS development. Whether circular RNA ASPH (circASPH) is involved in PCOS need to be studied further. We utilized RT‐qPCR to measure the expression levels of circASPH, miR‐375 and MAP2K6 in PCOS patients and normal group. The effects of circASPH and miR‐375 on KGN cells proliferation and apoptosis were observed by CCK‐8 assay, EdU incorporation assay and apoptosis assay, separately. Then Dual‐luciferase reporter assay was carried out to verify the circASPH/miR375 axis and miR375/MAP2K6 axis. The interaction between circASPH and MAP2K6 were detected with the support of RT‐qPCR and Western blot. We found circASPH and MAP2K6 were both over‐expressed in PCOS patients, while miR‐375 was in the opposite direction. Moreover, miR‐375 was negatively regulated by circASPH, while MAP2K6 was positively regulated by circASPH. In addition, circASPH directly targeted miR‐375, which targeted MAP2K6. More than that, the knockdown of circASPH repressed KGN cells proliferation and enhanced apoptosis, while the silence of miR‐375 reversed the above effects. In conclusion, circASPH promotes KGN cells proliferation through miR‐375/MAP2K6 axis in PCOS, and they are thought‐provoking biomarkers for PCOS diagnosis and therapy.